2013
DOI: 10.1590/s2176-94512013000200019
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of orthodontic treatment in adults: the conduct in orthodontist/patient relationship

Abstract: Introduction:The high demand for orthodontic treatment, evidenced over the last few decades, has been justified mainly by the greater importance given to facial esthetics, influencing individual's self esteem. However, the professional frequently does not meet all the patient's expectations, for not establishing good communication and not knowing about the critical points during orthodontic treatment. Objective: The aim of this study was to elucidate patients' desires and doubts regarding orthodontic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 21 publications
3
40
0
1
Order By: Relevance
“…This questionnaire was present with acceptable validity and reliability. Two studies were conducted as a survey with a limited sample size of 50 and 60 subjects [ 23 , 24 ], respectively. Finally, Zhang et al adopted the Child Perception Questionnaire (CPQ 11-14 ) to measure patient expectations on oral related quality of life during treatment procedures [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This questionnaire was present with acceptable validity and reliability. Two studies were conducted as a survey with a limited sample size of 50 and 60 subjects [ 23 , 24 ], respectively. Finally, Zhang et al adopted the Child Perception Questionnaire (CPQ 11-14 ) to measure patient expectations on oral related quality of life during treatment procedures [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight papers with four kinds of questionnaires measured patient expectations on orthodontic treatment experiences [Additional file 3 ]. The primary factors investigated in all these questionnaires were anticipated changes in social activity [ 12 , 22 27 ]; the duration of treatment [ 12 , 22 27 ]; types of treatment [ 12 , 22 27 ]; pain problems [ 12 , 20 , 22 , 24 27 ]; situation during the initial appointment [ 12 , 22 , 23 , 25 27 ]; frequency of revisit [ 12 , 22 , 23 , 25 27 ]; restriction in oral function such as eating [ 12 , 20 , 22 , 24 27 ]; restriction in oral hygiene [ 23 , 24 ]; relationship with orthodontists [ 23 , 24 ]; proficiency of dentist [ 24 ] and treatment complications [ 23 ]. E xpectations with regards to the treatment outcome and benefits .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women tend to visit the orthodontic clinics more than men [3]. The motivating factor for females to seek orthodontic treatment seems to be for enhancing facial aesthetics [4]. Similar trends have been reported worldwide [5][6][7].…”
Section: Introductionmentioning
confidence: 65%
“…Specifically, both the fear of pain frequently associated with treatment and the length of time in treatment are the concerns most often cited by potential patients as the barriers to treatment acceptance. A survey of orthodontic patients indicated that 58.3% cited orthodontic pain as their primary complaint, followed by treatment duration [1]. Jones and Chan concluded that compliance with orthodontic treatment may be predicated on the amount of discomfort and pain experienced at the onset of treatment [2].…”
Section: Introductionmentioning
confidence: 99%